Deficits in Trabecular Bone Microarchitecture in Young Women With Type 1 Diabetes Mellitus. (August 2015) - Abdalrahaman, Naiemh; McComb, Christie; Foster, John E; McLean, John; Lindsay, Robert S; McClure, John; McMillan, Martin; Drummond, Russell; Gordon, Derek; McKay, Gerard A; Shaikh, M Guftar; Perry, Colin G; et al.
ABSTRACT The pathophysiological mechanism of increased fractures in young adults with type 1 diabetes mellitus (T1DM) is unclear. We conducted a case‐control study of trabecular bone microarchitecture and vertebral marrow adiposity in young women with T1DM. Thirty women with T1DM with a median age (range) age of 22.0 years (16.9, 36.1) attending one outpatient clinic with a median age at diagnosis of 9.7 years (0.46, 14.8) were compared with 28 age‐matched healthy women who acted as controls. Measurements included MRI‐based assessment of proximal tibial bone volume/total volume (appBV/TV), trabecular separation (appTb.Sp), vertebral bone marrow adiposity (BMA), and abdominal adipose tissue and biochemical markers of GH/IGF‐1 axis (IGF‐1, IGFBP3, ALS) and bone turnover. Median appBV/TV in cases and controls was 0.3 (0.22, 0.37) and 0.33 (0.26, 0.4), respectively (p = 0.018) and median appTb.Sp in T1DM was 2.59 (2.24, 3.38) and 2.32 (2.03, 2.97), respectively (p = 0.012). The median appBV/TV was 0.28 (0.22, 0.33) in those cases with retinopathy (n = 15) compared with 0.33 (0.25, 0.37) in those without retinopathy (p = 0.02). Although median visceral adipose tissue in cases was higher than in controls at 5733 mm3 (2030, 11, 144) and 3460 mm3 (1808, 6832), respectively (p = 0.012), there was no difference in median BMA, which was 31.1% (9.9, 59.9) and 26.3% (8.5, 49.8) in cases and controls, respectively (p = 0.2). Serum IGF‐1 and ALS were also lower in cases, and the latter showed an inverse association to appTbSp (r = –0.30, p = 0.04). Detailed MRI studies in young women with childhood‐onset T1DM have shown clear deficits in trabecular microarchitecture of the tibia. Underlying pathophysiological mechanisms may include a microvasculopathy. © 2015 American Society for Bone and Mineral Research.